EVALUATION OF ANTISTRESS ACTIVITY OF EXTRACT OF TINOSPORA CORDIFOLIA & ASPARAGUS RACEMOSUS IN RATS - Biswas, Partha; Saha, Achintya (International Journal of Ayurveda and Pharma Research, 2015)
Objectives: Present study was undertaken to evaluate the adaptogenic and antistress activity of T. cordifolia & A.racemosus we investigated the antistress activity of T. cordifolia and A. racemosus by Cold Water Swim Stress Model in rats. Materials and Methods: The anti-stress activity was evaluated on Cold Water Swim Stress induced biochemical changes. Extract of T.cordifolia and A.racemosus was administered orally 400 mg /kg.b.wt. Diazepam (5 mg/ kg.b.wt was used as a gold standard. Serum lipid, serum glucose, plasma cortisol, plasma glutathione total plasma NO and lipid peroxidation in terms of MDA were used as the stress indices. Results: The level of total plasma nitric oxide, (NO), MDA, a lipid peroxidation marker and cortisol were significantly higher in rats with chronic stress compared with healthy control group (p<0.005). Both extract of T.cordifolia and A.racemosus reduced Stress induced lipid peroxide, serum glucose, and serum triglyceride and significantly enhance the plasma glutathione level compared with stress control group (p <0.005). Conclusion: The present findings strongly suggested that oxidative stress plays a significant role in the pathophysiology of chronic stress. The findings of the present study indicate that the herbal agents T.cordifolia and A.racemosus has significant antistress and adaptogenic activity as shown by its mitigating effects on several chronic stress induced biochemical perturbations, comparable to that induced by the well known antistress agent Diazepam.